2013
DOI: 10.1111/cid.12079
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of Keratinized Tissues for Dental Implants: A Clinical, Immunological, and Radiographic Study

Abstract: Based on the results of this study, it can be suggested that FGG performed around DIs lacking KT is a reliable method, leading to significant improvements in clinical and inflammatory parameters. Further long-term studies including more DIs are needed to clarify the role of KT on maintenance of DIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 54 publications
3
86
2
4
Order By: Relevance
“…The two CCTs were judged as having an unclear (Buyukozdemir Askin et al., ) or high (Roccuzzo, Grasso & Dalmasso, ) risk of selection (random sequence generation) bias. There was insufficient information regarding randomization allocation in one study (Buyukozdemir Askin et al., ), whereas in the other study, patients were allocated to a specific treatment according to the clinician's judgment (Roccuzzo et al., ). Concerning outcome and reporting bias, both CCTs were judged having a low risk.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two CCTs were judged as having an unclear (Buyukozdemir Askin et al., ) or high (Roccuzzo, Grasso & Dalmasso, ) risk of selection (random sequence generation) bias. There was insufficient information regarding randomization allocation in one study (Buyukozdemir Askin et al., ), whereas in the other study, patients were allocated to a specific treatment according to the clinician's judgment (Roccuzzo et al., ). Concerning outcome and reporting bias, both CCTs were judged having a low risk.…”
Section: Resultsmentioning
confidence: 99%
“…The therapeutic interventions were therefore indicated and performed in patients with existing implants and reconstructions. This included more specifically: implants with (i) signs of mucositis and a width of KT ≤1.5 mm (Basegmez et al., ), (ii) a width of KT ≤2 mm (Buyukozdemir Askin et al., ), (iii) a width of ≤1 mm (Lorenzo et al., ), or (iv) no KM (Roccuzzo et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that a sufficient amount of KM may contribute to reduce risk for and severity of peri‐implant mucositis. Unanimously, recent prospective clinical trials have found improvement of inflammatory parameters in dental implants with insufficient KM after free gingival grafts in comparison with maintenance alone (Buyukozdemir Askin et al, ; Oh, Masri, Williams, Ji, & Romberg, ). Future research may include a larger patient population to verify our findings, and prospective trials may identify the predictive value of the steady target variable mGI‐BoP and investigate if KM < 2 mm is a risk factor for peri‐implantitis.…”
Section: Discussionmentioning
confidence: 99%
“…One long-term study demonstrated that in patients receiving regular maintenance for an implant-supported fixed prosthesis, the width of keratinized mucosa had no effect on plaque accumulation on buccal sites, but significantly higher plaque accumulation was noted in implants on lingual sites where the width of keratinized mucosa was <2 mm. 22 In addition, Buyukozdemir Askin et al 23 found that implant sites with narrow keratinized mucosa (2 mm) had higher plaque score than did sites with wide keratinized mucosa (>2 mm), and they showed that the group with narrow keratinized mucosa had significant improvement of plaque index after gingival grafting procedure. These studies indicated that the presence of keratinized mucosa is not absolutely necessary for plaque control of the implant, but the existence of a band of keratinized mucosa provides a favorable environment to perform daily oral hygiene, which is advantageous for the patients with reduced manual dexterity.…”
Section: Influence Of Keratinized Mucosa On Oral Hygiene Practicementioning
confidence: 99%